Foreword to the special issue devoted to recreational science - García Molina, Rafael (Revista Eureka sobre Enseñanza y Divulgación de las Ciencias, 2011)
A short overview of the section devoted to recreational science is presented, together with a brief description of each one of the papers that are published in this issue.